Case Report: Effect of medicinal cannabis on fitness to drive in a patient with Tourette Syndrome and ADHD - Streetz, Charlotte Marie; Szejko, Natalia; Pisarenko, Anna; Fremer, Carolin; Teske, Jörg; Brunnauer, Alexander; Müller-Vahl, Kirsten R. (Frontiers in Psychiatry, 2025)
BackgroundTourette Syndrome (TS) is a childhood onset chronic disorder in which motor and vocal tics co-occur. Cannabinoids are a potential therapeutic option for otherwise treatment resistant patients. However, there is an ongoing debate regarding potential side effects. This is particularly important in relation to activities being necessary for daily life such as driving a car.Case presentationWe present the case of a 28-year-old male with TS and comorbid attention-deficit/hyperactivity disorder (ADHD) who was medicated by his treating physician with an extremely high dose of inhaled medicinal cannabis (MC) of up to 10 g/d. We were interested in the effects of MC on patient’s fitness to drive as well as corresponding serum levels of tetrahydrocannabinol (THC) and its metabolites. Therefore, clinical assessments and computer-based tests (Vienna Test System) were performed at different time points at two consecutive days before and after intake of MC at a dose that was determined by the patient according to clinical need. On day 1, he inhaled a total dose of 3.3 g and 4.1 g MC, respectively, before driving tests were performed. Until the end of the day, he used a total dose of 8.8 g. On day 2, he took no MC before all tests were completed. Remarkably, according to the German Federal Highway Research Institute guidelines, the patient was considered fit to drive in all domains assessed at all time points at day 1 and 2. Higher doses of MC – and corresponding very high THC serum levels – resulted in best results with respect to patient’s driving ability. THC serum levels ranged from 19 ng/ml (at day 2 without MC intake at this day) to 364 ng/ml (at day 1 after intake of a total of 3.3 g MC at the same day). No clinically relevant side effects occurred.ConclusionsThis case study demonstrates that patients with TS plus comorbid ADHD may be fit to drive even after intake of high doses of MC. In any case, however, every driver, who uses MC, is obliged to check fitness to drive before driving a vehicle.